2012
DOI: 10.1038/icb.2012.1
|View full text |Cite
|
Sign up to set email alerts
|

Epicutaneous immunization with DNP‐BSA induces CD4+ CD25+ Treg cells that inhibit Tc1‐mediated CS

Abstract: As we have shown previously that protein antigen applied epicutaneously (EC) in mice inhibits TNP-specific Th1-mediated contact sensitivity (CS), we postulated that the maneuver of EC immunization might also suppress Tc1-dependent CS response. Here we showed that EC immunization of normal mice with 2,4-dinitrophenylated bovine serum albumin (DNP-BSA) applied on the skin in the form of a patch induces a state of subsequent unresponsiveness due to regulatory T cells (Treg) that inhibited sensitization and elicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…These data suggest that EC-induced suppressor cells are very efficient regulators. This is consistent with our previous observation that small numbers of purified TCRαβ + suppressor cells can ameliorate the inflammatory response, since only 2.5 × 10 3 sorted cells efficiently inhibits CHS and EAE [15][16][17] .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These data suggest that EC-induced suppressor cells are very efficient regulators. This is consistent with our previous observation that small numbers of purified TCRαβ + suppressor cells can ameliorate the inflammatory response, since only 2.5 × 10 3 sorted cells efficiently inhibits CHS and EAE [15][16][17] .…”
Section: Discussionsupporting
confidence: 81%
“…In summary, induction of tolerance via EC immunization with protein antigen can inhibit cell-mediated immune responses in an animal model of RA, as we have previously demonstrated in CHS [14,15] , allogeneic skin graft rejection [19] and TNBS-induced colitis [18] , as well as in an animal model of multiple sclerosis [16,17,58] and in patients with multiple sclerosis [20,21] . This method may therefore be useful for the treatment of a variety of inflammatory diseases.…”
Section: Foxp3mentioning
confidence: 98%
See 1 more Smart Citation
“…Then, we found that EC immunization with myelin basic protein (MBP) prior to induction of experimental model of multiple sclerosis (EAE) resulted in protection from developing disease [9,24,25]. More recently, we showed that EC immunization with protein antigen suppresses Tc1-dependent and NK cell mediated CS to DNP [10,11] and an animal model of skin graft rejection [8]. Then, experiments in an animal model of arthritis [collagen induced arthritis (CIA)] showed that EC immunization with collagen prior to CIA induction alleviates disease [21].…”
Section: Discussionmentioning
confidence: 99%
“…Ear punches were transferred to tubes containing 1 ml of formamide. After 18 h incubation at 37°C the samples were centrifuged and the optical density (OD) of the supernatant fluids was read at 565 nm against blank containing formamide alone (Majewska- Szczepanik et al, 2012).…”
Section: Vascular Permeability Testmentioning
confidence: 99%